LITHOSPHERE STRUCTURE OF THE UKRAINIAN SHIELD AND PRIPYAT TROUGH IN THE REGION OF EUROBRIDGE-97 (UKRAINE AND BELARUS) FROM GRAVITY MODELLING - Yegorova T.P.; Starostenko V.I.; Kozlenko V.G.; Yliniemi J. (My University, 2004)
The southern segment of the seismic profile EUROBRIDGE—EUROBRIDGE-97 (EB'97)—located in Belarus and Ukraine, crosses the suture zone between two main segments of the East European Craton—Fennoscandia and Sarmatia—as well as Sarmatia itself. At the initial stage of our study, a 3-D density model has been constructed for the crust of the study region, including the major part of the Osnitsa–Mikashevichi Igneous Belt (OMIB) superimposed by sediments of the Pripyat Trough (PT), and three domains in the Ukrainian Shield—the Volhyn Domain (VD) with the anorthosite–rapakivi Korosten Pluton (KP), the Podolian Domain (PD), and the Ros–Tikich Domain (RTD). The model comprises three layers—sediments with maximum thickness (6 km) in the PT and two heterogeneous layers in the crystalline crust separated at a depth of 15 km. 3-D calculations show the main features of the observed gravity field are caused by density heterogeneities in the upper crust. Allocation of density domains deeper than 15 km is influenced by Moho topography. Fitting the densities here reveals an increase (up to 2960 kg m−3) in the modelled bodies accompanied by a Moho deepening to 50 km. In contrast, a Moho uplift to a level of 35–37 km below the KP and major part of the PT is associated with domains of reduced densities. An important role for the deep Odessa–Gomel tectonic zone, dividing the crust into two regions one of basically Archean consolidation in the west (PD and RTD) and one of Proterozoic crust in the east (Kirovograd Domain)—was confirmed.
Keywords: 3-D gravity modelling; Crustal structure and composition; Precambrian Ukrainian Shield; Pripyat Trough; Korosten Pluton; Rapakivi–anorthosite; Precambrian::Archean; Докембрий::Архей